Isolamento de antocianinas monoméricas de elevada pureza utilizando técnica de extração em fase sólida - Pauletto, Roberson (2019)
Anthocyanins are pigments of plant origin, belonging to the group of flavonoids. Their color may vary from orange-red to blue-violet. Red fruits (strawberry, blackberry, blueberries, among others) are considered rich sources in these compounds. High purity isolated anthocyanins are important in the area of laboratory analysis, being used as analytical standards and in studies that aim to verify their bioactive potential. Due to the high cost and low availability of commercial analytical standards, research has been carried out to isolate anthocyanins from plant sources. Existing anthocyanin separation and isolation techniques from plant extracts require sophisticated and costly maintenance equipment. Because of this, the present work aimed to develop a technique of purification of monomeric anthocyanins using solid phase extraction cartridges (SPE) to obtain high purity anthocyanin standard from aqueous extracts of strawberry (Fragraria x ananassa Duch) and blackberry (Rubus sp.). The methodology was based on the solid phase extraction technique with SPE C18 1g cartridges using ultrapure water and methanol (22%) gradients, both acidified with 0.35% formic acid (v/v), to obtain collection anthocyanin-rich fractions. The method exhibited great efficiency for the isolation of high purity (≥95%) pelargonidin-3-O-glucoside from aqueous extract of strawberry, isolated anthocyanin exhibiting excellent storage stability (60 days). Great efficiency was also obtained for the isolation of high purity (≥96%) cyanidin-3-O-glucoside (Cy3G) from blackberry extract, using the same method with some modifications. Cy3G had excellent storage stability (90 days). The method also demonstrated good reproducibility in the isolation of high purity anthocyanins when tested using different cultivars and brands of SPE cartridges. The results presented in this research demonstrate the possibility of obtaining analytical standards quickly, practically and with high purity, becoming a viable alternative for application in studies that can more accurately evaluate the effects of these anthocyanins and their mechanisms of action.